The Impact of the Think Talk Write Cooperative Learning Model on the Narrative Writing Skills of Fifth-Grade Students at SD Negeri 114 Mallenreng Sinjai Regency - Wulandari, Selfiana Wulandari; Rohana; Yusuf, Faidah (PT Ininnawa Paramacitra Edukasi, 2024)
This research was an experimental study that aimed to 1) describe the use of the cooperative learning model type Think Talk Write in grade V, 2) describe the narrative text writing skills of grade V students, and 3) determine the effect of the Think Talk Write cooperative learning model on the writing skills of grade V students at SD Negeri 114 Mallenreng, Sinjai Regency. This pre-experimental study used a one-group pretest-posttest design. The population consisted of all 18 grade V students at SD Negeri 114 Mallenreng. The independent variable was the Think Talk Write cooperative learning model, and the dependent variable was narrative text writing skills. The research procedure was conducted in three stages: preparation, implementation, and evaluation. Data collection techniques included observation, tests, and documentation, with Pretest, Treatment, and Posttest administered. The research adopted a quantitative approach, with data analysis involving prerequisite tests such as the normality test and hypothesis test. The final analysis was performed using paired sample tests in SPSS. The results of the study reveal: 1) the Think Talk Write cooperative learning model is implemented effectively according to the planned steps, 2) the writing skills of grade V students are categorized as sufficient before treatment and improve to good after treatment, and 3) the use of the Think Talk Write cooperative learning model has a positive impact on the writing skills of grade V students at SD Negeri 114 Mallenreng.